PERLINDUNGAN HUKUM BAGI PEMENANG LELANG OBYEK HAK TANGGUNGAN DARI GUGATAN PERDATA PIHAK KETIGA - Angga, Firman (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
In practice, the auction, although carried out in accordance with applicable regulations, is sometimes still sued in the District Court, the High Court even to the Supreme Court. The results of the supreme court's decision were canceled. Regarding this matter, of course the auction winner is very disadvantaged. The problem to be known in this scientific work is a form of legal protection against the winning bidder for the execution of Mortgage, and how to settle if there are obstacles in the implementation of the auction. This scientific work uses a normative juridical method with a statute approach, a conceptual approach and a case approach. The results obtained from this study are that the form of legal protection for auction winners who have good intentions is: 1) Submitting resistance (Derden Verzet) to the execution of the verdict. This resistance is submitted to the Chairperson of the District Court whose confiscation occurs in his jurisdiction, both verbally and in writing, 2) Submitting a request for legal protection for the decision to cancel the auction and re-execute. The method of settlement if there is an obstacle in the implementation of the auction for the Mortgage by means of the debtor paying the amount of debt and other costs as stated in the contents of the decision if the obstacles arise during the auction. Whereas the method of settlement after the auction, is the creditor as the buyer and the winner of the auction of the Mortgage resistance (derden verset) by suing the debtor to court with a claim for compensation for all costs of conducting the auction that has been carried out and canceled by the court. Furthermore, Bank Rakyat Indonesia as the creditor holds the default debtor accountable to immediately fulfill the defaulted debt by re-executing